A study on role of sputum conversion rate in management of tuberculosis in South Indian population - Bineni, Chandrasekhar; Yarasani, Pradeep; Ravi Prabhu, G. (International Journal Of Community Medicine And Public Health, 2018)
Background: Directly observed treatment short course (DOTS) is the currently recommended control strategy for tuberculosis. Even after intensive phase of directly observed treatment short course, there is delayed sputum smear conversion in some patients due to multiple factors. The present study was undertaken to study the role of sputum conversion in management of tuberculosis. Methods: A total of 229 patients with smear positive Tuberculosis cases of both Category-I and Category-II from DOTS centre in tuberculosis, S.V.R.R. Government General Hospital, Tirupati, A.P were enrolled and registered for the present study. Consent was taken from the patients to study the role of Sputum conversion rate importance in management of Tuberculosis in South Indian population. Results: The sputum conversion rate has been found to be higher in Category I (93.2%) compared to that of Category II (80.8%) and the difference is also found to be statistically significant. The sputum conversion rate has been found to be higher in those who were one + initial grade of sputum 96.1% followed by scanty grading 93.3%. Conclusions: The present study suggests that special attention should be given to patients enrolled for DOTS II regimen to improve sputum conversion rate in management of tuberculosis.